Is Covid-19 or Coronavirus a work of Art, as informed by my new 5-pointer ART THEORY - ANTOA? - WILL, RALF G (IJRDO - Journal of Social Science and Humanities Research, 2021)
According to my NEW THEOREM OF ART – ANTOA, a work of creativity displays relevance, sincerity as well as social context, and is up to date, when it complies with at least 3 of the following 5 points: 1) Individual history/footprint or personality: The work needs to contain an individual statement by artist, express his personal preference or reflect sincere creative character.2) Social context: Show social relevance, weave work in socio-historical background, deal with issues pertaining to the communal or social value of human existence.3) Old and new meet: Did the artist innovate, revolutionize an old, known technique to create a new, emotionally and spiritually relevant viceversa appealing message?4) Abstraction: How did the artist explain or present the abstract side of creation, as eg in visual artistry, in poetry, even in photography? Does he/she give viewers, consumers, readers etc., an idea to or explanation of abstraction, eg tells us where it came from and where it leads us to, or is interpretation solely left to our own making, without any hints at why such a colour blotch or specific shape or repetitive, sliced and peeled off pattern expresses creativity?   5) Message, value, symbolism: Does the work contain a message that touches our emotional,       personal, inner level, adds value or signifies why we should see the work as Art?